A Case of Extramedullary Plasmacytoma of the Biliary Tract with a Poor Prognosis - Eiko Sakurai; Kazunori Nakaoka; Seiji Yamada; Naoe Goto; Akihiro Tomita; Yoshiki Hirooka; Tetsuya Tsukamoto (Reports, 2022)
Extramedullary plasmacytoma (EMP) is a rare disease consisting of the presence of monoclonal plasma cells in tissues other than the bone. Most EMPs are located in the head and neck region. We present an extremely rare case of an EMP originating from the biliary tract in a 76-year-old male. This is the fifth report of a primary EMP arising from the biliary tract. He was diagnosed with jaundice, and he was referred for an additional examination. Abdominal ultrasonography revealed a tumor in the gallbladder and bile ducts, and a bile duct biopsy was performed via endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA). The pathological and immunohistochemical examination revealed that the tumor was a plasmacytoma originating in the biliary tract. Although endoscopic biliary drainage was performed, the bile duct infection was not well controlled due to obstructive jaundice caused by the tumor. Furthermore, the bleeding from the tumor during chemotherapy was uncontrolled. Pancreaticoduodenectomy and cholecystectomy were performed to control the infection and bleeding. Although chemotherapy was continued after surgery, the tumor of the intrahepatic bile duct enlarged. He died seven months after the diagnosis because of the treatment-resistant tumor.